The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/jfn.0000000000000209
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Human Papillomavirus Prevention During Pediatric Acute Sexual Assault Care

Abstract: Significant barriers to addressing HPV in the ED setting exist, most significantly reliance on caregiver recall to guide vaccination administration, raising concern for overvaccination and undervaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“… 71 , 75 , 81 , 82 , 86 , 91 , 95 , 97 , 99 , 101 , 107 , 109 111 , 113 , 115 , 117 , 119 , 127 About 22 (31%) studies focused specifically on child sexual assault cases, 70 , 79 , 80 , 96 , 98 , 106 , 112 , 116 , 118 , 120 , 123 , 125 , 130 , 132 , 133 , 141 with six of these studies looking at sexually transmitted infection (STI) and pregnancy testing, STI prophylaxis, and the use of sexual assault nurse examiners. 77 , 78 , 121 , 122 , 140 , 150 Two of three review publications focused on screening, 154 , 155 with one publication focusing on improving the ED workflow for suspected or confirmed child abuse cases. 156 …”
Section: Resultsmentioning
confidence: 99%
“… 71 , 75 , 81 , 82 , 86 , 91 , 95 , 97 , 99 , 101 , 107 , 109 111 , 113 , 115 , 117 , 119 , 127 About 22 (31%) studies focused specifically on child sexual assault cases, 70 , 79 , 80 , 96 , 98 , 106 , 112 , 116 , 118 , 120 , 123 , 125 , 130 , 132 , 133 , 141 with six of these studies looking at sexually transmitted infection (STI) and pregnancy testing, STI prophylaxis, and the use of sexual assault nurse examiners. 77 , 78 , 121 , 122 , 140 , 150 Two of three review publications focused on screening, 154 , 155 with one publication focusing on improving the ED workflow for suspected or confirmed child abuse cases. 156 …”
Section: Resultsmentioning
confidence: 99%
“…Data collection in two studies was in-depth interviews with children and their parents [ 37 , 39 ]. Although most contents included all medical, psychological, forensic, and legal services for victims of sexual abuse, some addressed only one of the psychological [ 37 ], forensic [ 33 ], or HPV (Human Papilloma Virus) vaccination measures [ 36 ]. The quality of evidence was relatively good as can be seen in Tables 1 and 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the national clinical practice guidelines suggested HPV vaccination is needed after child sexual abuse [ 29 ]. Two studies on child victims of sexual abuse also showed the effectiveness and importance of the HPV vaccine in post-rape care [ 36 , 40 ]. HPV vaccination should be given to children between the ages of 9–14 years [ 2 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Among adult women who suffer sexual violence, the incidence of human papillomavirus (HPV) varies between 2% and 40%. 8,18,25 A longitudinal study, controlled and randomized with 665 young American women who had suffered sexual violence in the previous 12 months, showed a 4.5 times greater chance of testing positive for HPV 16 or 18 in the cervix, suggesting sexual violence as a risk factor for infection. 26 The current 2015 Centers for Disease Control and Prevention (CDC) has updated their recommendations for sexually assaulted patients to now receive the HPV vaccine.…”
Section: Discussionmentioning
confidence: 99%